2013
DOI: 10.1111/tri.12191
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil and platelet-to-lymphocyte ratio as new predictors of dropout and recurrence after liver transplantation for hepatocellular cancer

Abstract: Summary There is increasing evidence that systemic inflammation markers like neutrophil (NLR) and platelet‐to‐lymphocyte ratios (PLR) may play a role in the outcome of hepatocellular cancer (HCC). Between January 1994 and March 2012, 181 patients with HCC were registered on the transplant waiting list: 35 (19.3%) patients dropped out during the waiting period and 146 (80.7%) patients underwent liver transplantation (LT). The median follow‐up of this patient cohort was 4.2 years (IQR: 1.8–8.3). On c‐statistics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 38 publications
7
113
2
1
Order By: Relevance
“…Instead, NLR and PLR, calculated from leukocyte differential counts and platelet counts, respectively, are more readily available and inexpensive compared to CRP (7). Notably, numerous previous studies have already indicated that an elevated NLR and PLR is associated with a poorer survival in patients with ovarian (8), breast (9,10), non-small cell lung (11), esophageal (12,13), gastric (7,14) and hepatocellular cancers (15) and CRC (2,(16)(17)(18). NLR is the ratio of the absolute neutrophil count to the absolute lymphocyte count, and therefore the association between a high NLR and a poor prognosis, as revealed in the present study, is possibly indicative of the tumor-promoting activity associated with neutrophilia in the tumor environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, NLR and PLR, calculated from leukocyte differential counts and platelet counts, respectively, are more readily available and inexpensive compared to CRP (7). Notably, numerous previous studies have already indicated that an elevated NLR and PLR is associated with a poorer survival in patients with ovarian (8), breast (9,10), non-small cell lung (11), esophageal (12,13), gastric (7,14) and hepatocellular cancers (15) and CRC (2,(16)(17)(18). NLR is the ratio of the absolute neutrophil count to the absolute lymphocyte count, and therefore the association between a high NLR and a poor prognosis, as revealed in the present study, is possibly indicative of the tumor-promoting activity associated with neutrophilia in the tumor environment.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the scope and effects of an inflammatory reaction have always been assessed according to a number of biochemical markers, including the neutrophil lymphocyte ratio (NLR) and platelet lymphocyte ratio (PLR), which are inexpensive markers of systemic inflammation (7). Previous studies have indicated that elevated NLR or PLR suggested a poor prognosis for various types of cancer, including ovarian (8), breast (9,10), non-small cell lung (11), esophageal (12,13), gastric (7,14), hepatocellular (15) and CRC (2,(16)(17)(18). However, the current literature leaves certain questions unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In all studies, 2-5 approximately 30% of the patients were outside the Milan criteria; however, there was no analysis of inflammatory markers in association with these criteria apart from 1 study. 2 In that study, patients outside the Milan criteria with high NLRs had significantly worse tumor-free survival than those with low NLRs.…”
Section: To the Editorsmentioning
confidence: 99%
“…Hepatocellular cancer is the fifth tumor-related cause of death, and associated with a significant rate of postoperative relapse even with complete excision, such as during liver transplantation [1]. Increased aggressiveness of minimal residual disease and immune cells activity modulation may play a role in the perioperative period.…”
Section: Patrice Forgetmentioning
confidence: 99%
“…Increased aggressiveness of minimal residual disease and immune cells activity modulation may play a role in the perioperative period. In particular neutrophils are associated with the activation of protumoral processes, whereas some T lymphocytes can exert an antitumoral role [1][2][3]. These observations have triggered considerations for specific interventions during surgery, to limit the proliferative activity of cancer cells, such as to improve anticancer immune activity [4].…”
Section: Patrice Forgetmentioning
confidence: 99%